PENDAPATAN DAN PENGELUARAN RUMAH TANGGA PEDESAAN DAN KAITANNYA DENGAN TINGKAT KEMISKINAN - SUPADI -; ACHMAD ROZANY NURMANAF (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
Study conducted in 3 province, these are Central Java, Lampung and South Sulawesi. Ineach province choice 4 villages classified by agroecosystem, i.e wet land villages anddry land villages. In every village interviewed 50-60 households as the Patanashousehold sample. The purpose of the study is to inform household income, especiallyper capita income and expenditure that relate to poverty level. This is based onSayogyo, World Bank and BPS criteria, beside structure and distribution of householdincome. The result of study showed that according to Sayogyo and BPS criteriahousehold in both agroecosystem, wet land and dry land, are not fall into povertycriteria. But, by using the World Bank criteria the household of the village falls intopoverty criteria. While, income structure is still dominated by agricultural sector, but theroll of non-agricultural sector increate gradually. Household income distribution falls inhighly inequality classification.